IRS-assisted full-duplex ISAC system beamforming design - LIU Qilie; WANG Long; XIN Yanan; FANG Jiacheng; CHEN Qianbin; TAO Yu (Dianxin kexue)
To address the issues of frequency switching differences between communication and sensing systems in traditional integrated sensing and communication (ISAC) scenarios, as well as the susceptibility of communication to obstruction by obstacles, the integration of full-duplex (FD) technology and intelligent reflecting surface (IRS) into the ISAC system was studied. The design of FD beamforming assisted by IRS in the ISAC scenario was investigated. An optimization problem for maximizing the user rates of uplink and downlink beamforming was formulated, considering constraints on IRS phase shift, base station receiving beamforming, the maximum transmission power of the base station, the maximum transmission power of uplink users, and the radar sensing threshold. The original non-convex problem was solved by being transformed into a convex optimization problem through the use of alternating optimization, continuous convex approximation, semi-definite relaxation, variable substitution, and semi-definite programming. Simulation results show that the proposed scheme resulted in an 89.02% enhancement under the communication performance indicators considered compared to the corresponding half-duplex scheme and a 70.15% improvement over the random IRS scheme.